Analisis Produktivitas Kerja Karyawan Pada CV Griya Alam Mulya - Adhitya Pratama Wisnuwardhana; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Manajemen Riset Inovasi, 2024)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The aim of this research is to determine employee work productivity at CV Griya Alam Mulya which includes the impact of employee work productivity at CV Griya Alam Mulya, as well as supporting factors that support the achievement of optimal work productivity. From the results of this research, it can be seen that the work productivity of employees at CV Griya Alam Mulya is quite good. Although there are several obstacles that can hinder work, high morale and collaboration between employees helps overcome these obstacles and keep productivity high. This can be seen from the positive impact felt by CV Griya Alam Mulya, and the various factors supporting its work productivity.